Death of a liar : a Hamish Macbeth mystery - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries, 2015)
Sergeant Hamish Macbeth investigates the murder of a woman in the small village of Cronish in the Scottish Highlands who had lied about being brutally attacked.